Successful Patterns of Scientific Knowledge Sourcing: Mix and Match - Wolfgang Sofka; Birgit Aschhoff (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
Valuable knowledge emerges increasingly outside of firm boundaries, in particular in public research institutions and universities. The question is how firms organize their interactions with universities effectively to acquire knowledge and apply it successfully. Literature has so far largely ignored that firms may combine different types of interactions with universities for optimizing their collaboration strategies. We argue conceptually that firms need diverse (broad) and highly developed (deep) combinations of various interactions with universities to maximize returns from these collaborations. Our empirical investigation rests upon a survey of more than 800 firms in Germany. We find that both the diversity and intensity of collaborative engagements with universities propel innovation success. However, broadening the spectrum of interactions is more beneficial with regard to innovation success. Applying latent class cluster analysis we identify four distinct patterns of interaction. Our findings show that formal forms of interaction (joint/contract) research provide the best balance between joint knowledge development and value capture.
More recent version: http://hdl.handle.net/10419/27576
Keywords: C30; D83; O32; 330; Technology transfer; industry-science links; open innovation; university knowledge; Unternehmen; Industrielle Forschung; Forschungskooperation; Technologietransfer; Innovationsmanagement; Hochschule; Wissenstransfer; Deutschland